2020
DOI: 10.1101/2020.12.16.423141
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ecdysone coordinates plastic growth with robust pattern in the developing wing

Abstract: Animals develop in unpredictable, changing environments. To do this, they adjust their development according to environmental conditions to generate plastic variation in traits, while also buffering against environmental change to produce robust phenotypes. However, how organ development is coordinated to accommodate both plastic and robust developmental responses is poorly understood. Here, we propose that the steroid hormone ecdysone coordinates both plasticity in organ size and robustness of organ pattern i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 114 publications
0
1
0
Order By: Relevance
“…This biphasic, concentration-dependent regulation of regenerative activity allows ecdysone to coordinate regeneration with the duration of larval development. This coordinating role may be similar to how ecdysone coordinates imaginal disc patterning with the larval development period (Alves et al, 2020). Similarly, recently published experiments have observed that damage of the Drosophila hindgut during L2 or early L3 produces Dilp8, delaying the onset of pupariation, whereas damage to the hindgut of wandering L3 larvae no longer produces Dilp8 or developmental delay.…”
Section: Discussionmentioning
confidence: 54%
“…This biphasic, concentration-dependent regulation of regenerative activity allows ecdysone to coordinate regeneration with the duration of larval development. This coordinating role may be similar to how ecdysone coordinates imaginal disc patterning with the larval development period (Alves et al, 2020). Similarly, recently published experiments have observed that damage of the Drosophila hindgut during L2 or early L3 produces Dilp8, delaying the onset of pupariation, whereas damage to the hindgut of wandering L3 larvae no longer produces Dilp8 or developmental delay.…”
Section: Discussionmentioning
confidence: 54%